Glutathionylation chemistry promotes interleukin‐1 beta‐mediated glycolytic reprogramming and pro‐inflammatory signaling in lung epithelial cells. Issue 5 (4th April 2021) - Aboushousha, Reem; Elko, Evan; Chia, Shi B.; Manuel, Allison M.; van de Wetering, Cheryl; van der Velden, Jos; MacPherson, Maximilian; Erickson, Cuixia; Reisz, Julie A.; D'Alessandro, Angelo; Wouters, Emiel F. M.; Reynaert, Niki L.; et al.
Abstract: Glycolysis is a well‐known process by which metabolically active cells, such as tumor or immune cells meet their high metabolic demands. Previously, our laboratory has demonstrated that in airway epithelial cells, the pleiotropic cytokine, interleukin‐1 beta (IL1B) induces glycolysis and that this contributes to allergic airway inflammation and remodeling. Activation of glycolysis is known to increase NADPH reducing equivalents generated from the pentose phosphate pathway, linking metabolic reprogramming with redox homeostasis. In addition, numerous glycolytic enzymes are known to be redox regulated. However, whether and how redox chemistry regulates metabolic reprogramming more generally remains unclear. In this study, we employed a multi‐omics approach in primary mouse airway basal cells to evaluate the role of protein redox biochemistry, specifically protein glutathionylation, in mediating metabolic reprogramming. Our findings demonstrate that IL1B induces glutathionylation of multiple proteins involved in metabolic regulation, notably in the glycolysis pathway. Cells lacking Glutaredoxin‐1 ( Glrx), the enzyme responsible for reversing glutathionylation, show modulation of multiple metabolic pathways including an enhanced IL1B‐induced glycolytic response. This was accompanied by increased secretion of thymic stromal lymphopoietin (TSLP), a cytokine important in asthma pathogenesis. Targeted inhibition of glycolysis prevented TSLP release, confirming the functional relevance of enhanced glycolysis in cells stimulated with IL1B. Collectively, data herein point to an intriguing link between glutathionylation chemistry and glycolytic reprogramming in epithelial cells and suggest that glutathionylation chemistry may represent a therapeutic target in pulmonary pathologies with perturbations in the glycolysis pathway.